Vaginal Lactobacillus Inhibits HIV-1 Replication in Human Tissues Ex Vivo - Ñahui Palomino, Rogers A.; Zicari, Sonia; Vanpouille, Christophe; Vitali, Beatrice; Margolis, Leonid (Frontiers in Microbiology, 2017)
Lactobacillus species, which dominate vaginal microbiota of healthy reproductive-age women lower the risks of sexually transmitted infections, including the risk of HIV acquisition. The exact mechanisms of this protection remain to be understood. Here, we investigated these mechanisms in the context of human cervico-vaginal and lymphoid tissues ex vivo. We found that all six lactobacilli strains tested in these systems significantly suppressed HIV-1 infection. We identified at least three factors that mediated this suppression. (i) Acidification of the medium. The pH of the undiluted medium conditioned by lactobacilli was between 3.8 and 4.6. Acidification of the culture medium with HCl to this pH in control experiments was sufficient to abrogate HIV-1 replication. However, Lactobacillus-conditioned medium diluted five fold, which reached pH ~ 6.9 was also suppressive for HIV-1 infection while in control experiments HIV-1 infection was not abrogated when the pH of the medium was brought to 6.9 using HCl. This suggested the existence of other factors responsible for HIV-1 inhibition by lactobacilli. (ii) Lactic acid. There was a correlation between the concentration of lactic acid in the Lactobacillus-conditioned medium and its ability to suppress HIV-1 infection in human tissues ex vivo. Addition of lactic acid isomers D and L to tissue culture medium at the concentration that corresponded to their amount released by lactobacilli resulted in HIV-1 inhibition. Isomer L was produced in higher quantities than isomer D and was mostly responsible for HIV-1 inhibition. These results indicate that lactic acid, in particular its L-isomer, inhibit HIV-1 independently of lowering of the pH. (iii) Virucidal effect. Incubation of HIV-1 in Lactobacillus–conditioned medium significantly suppressed viral infectivity for human tissues ex vivo. Finally, lactobacilli adsorb HIV-1 serving as a sink decreasing the amount of free virions. In summary, we found that lactobacilli inhibit HIV-1 replication in human tissue ex vivo by multiple mechanisms. Further studies are needed to evaluate the potential of altering the spectra of vaginal microbiota as effective strategies to enhance vaginal health. Human tissues ex vivo may serve as a test system for these strategies.